PENINGKATAN KEMAMPUAN MOTORIK HALUS MELALUI KEGIATAN MERONCE PADA ANAK KELOMPOK B TK ISLAM NURUSSALAM KABUPATEN MAROS - Andi Junil Hera; Fadhilah Latief (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2020)
The main problem in this research is whether through meronce activities the fine motor skills of Islamic kindergarten students in Marus Regency can be improved. This study aims to describe improving fine motor skills through Meronce activities in B-Nurussalam Islamic Kindergarten, Maros Regency. This type of research is a group work room (group work room) consisting of two sessions, each session carried out up to three meetings. Research procedures include planning, implementation, monitoring and reflection. The subjects in this study were group B nuruslam group, Islamic kindergarten B group, with a total of 12 people. The results of the fine motor skills research for children can be seen from the average results of observing children's creativity in the first cycle which reached 52.91% with the attainment of development standards according to expectations (BSH) and the second session 85.41% with very good development standards (BSB) achieving the goal of achievement. Based on the results of the research that has been explained, it can be concluded that the precise motor skills of group B for kindergarten students of Noor Al Salam Islamic in Marous Regency can be improved through meronce activities using beads.